The Illumination of Thunderclouds by Lightning: 2. The Effect of GLM Instrument Threshold on Detection and Clustering. Issue 1 (10th January 2022) - Peterson, Michael; Light, Tracy E. L.; Mach, Douglas
Abstract: Lightning is measured from space using optical instruments that detect transient changes in the illumination of the cloud top. How much of the flash (if any) is recorded by the instrument depends on the instrument detection threshold. NOAA's Geostationary Lightning Mapper (GLM) employs a dynamic threshold that varies across the imaging array and changes over time. This causes flashes in certain regions and at night to be recorded in greater detail than other flashes, and threshold inconsistencies will impose biases on all levels of GLM data products. In this study, we quantify the impact of the varying GLM threshold on event/group/flash detection, flash clustering, and gridded product generation by imposing artificial thresholds on the event data taken from a thunderstorm with a low instrument threshold (∼0.7 fJ). We find that even modest increases in threshold severely impact event (60% loss by 2 fJ, 90% loss by 10 fJ) and group (25% loss by 2 fJ, 81% loss by 10 fJ) detection by suppressing faint illumination of the cloud top from weak sources and scattering. Flash detection is impacted less by threshold increases (4% loss by 2 fJ), but reductions are still significant at higher thresholds (35% loss by 10 fJ, or 44% if single‐group flashes are removed). Undetected pulses cause individual flashes to be split and severely impact the construction of gridded products. All of these factors complicate the interpretation of GLM data, particularly when trended over time under a changing threshold. Plain Language Summary: Lightning is measured from space by optical instruments like the Geostationary Lightning Mapper (GLM). GLM detects rapid changes in cloud brightness from lightning illumination. How much of this illumination can be captured depends on the sensitivity of the instrument, which, for GLM, changes over space and time according to the local instrument threshold. At a low threshold—like we see at night or near the center of the GLM Field of View ‐ flashes can be measured with a tremendous amount of detail. However, when the threshold is high—as it is during the day or in certain places like Colorado—only the brightest portions of a flash might be seen, if the flash is detected at all. In this study, we characterize the effect of the GLM instrument threshold on each type of GLM data. We find that removing faint detections by imposing higher thresholds affects every type of GLM data. These results demonstrate that situational context is important for evaluating GLM data—particularly when trended over time under a changing threshold. Key Points: Geostationary lightning mapper (GLM) sensitivity is determined by the local threshold at each instrument pixel, which varies across the imaging array and over time High thresholds prevent detection of faint illumination, which limits the resolvable detail of flashes or might prevent detection entirely Instrument threshold affects all GLM products from event detections to flash clustering and gridded product generation